Volcanic Flank Collapse, Secondary Sediment Failure and Flow‐Transition: Multi‐Stage Landslide Emplacement Offshore Montserrat, Lesser Antilles - Michel Kühn; Christian Berndt; Sebastian F. L. Watt; Matthew J. Hornbach; Sebastian Krastel; Kristina Sass; Steffen Kutterolf; Tim Freudenthal; Katrin Huhn; Jens Karstens; Bettina Schramm; Judith Elger; et al. (Geochemistry, Geophysics, Geosystems, 2024)
Abstract Volcanic flank collapses, especially those in island settings, have generated some of the most voluminous mass transport deposits on Earth and can trigger devastating tsunamis. Reliable tsunami hazard assessments for flank collapse‐driven tsunamis require an understanding of the complex emplacement processes involved. The seafloor sequence southeast of Montserrat (Lesser Antilles) is a key site for the study of volcanic flank collapse emplacement processes that span subaerial to submarine environments. Here, we present new 2D and 3D seismic data as well as MeBo drill core data from one of the most extensive mass transport deposits offshore Montserrat, which exemplifies multi‐phase landslide deposition from volcanic islands. The deposits reveal emplacement in multiple stages including two blocky volcanic debris avalanches, secondary seafloor failure and a late‐stage erosive density current that carved channel‐like incisions into the hummocky surface of the deposit about 15 km from the source region. The highly erosive density current potentially originated from downslope‐acceleration of fine‐grained material that was suspended in the water column earlier during the slide. Late‐stage erosive turbidity currents may be a more common process following volcanic sector collapse than has been previously recognized, exerting a potentially important control on the observed deposit morphology as well as on the runout and the overall shape of the deposit.